Significantly stable organic cathode for lithium-ion battery based on nanoconfined poly(anthraquinonyl sulfide)@MOF-derived microporous carbon. (1st March 2020) - Zhao, Liyi; Guan, Zhixing; Ullah, Zaka; Yu, Congcong; Song, Hewei; Chu, Rongrong; Zhang, Yingfei; Li, Weiwei; Li, Qi; Liu, Liwei
Abstract: The organic materials are auspicious alternative to the inorganic counterparts as cathode materials for lithium-ion batteries (LIBs) owing to their unusual capacity and sustainability. However, the widespread application of organic cathode in most of the cases have been hampered by their intrinsically easy solubility in electrolyte and natural insulating property, resulting in the poor practical capacity and low rate capacity. Herein, we demonstrate the rational 'ship in bottle' strategy to overcome these problems by confining the organic materials into microporous host. Poly(anthraquinonyl sulfide) (PAQS) was successfully polymerized inside a MOF-derived 3D microporous carbon (3D-C) to obtain PAQS@3D-C via 'ship in bottle' strategy. The novel organic cathode for LIBs shows a higher reversible specific capacity of 219 mAh g −1 at 0.2 C and greatly improved cycle life with low capacity fading speed of ∼0.015% per cycle. Specifically, PAQS@3D-C shows a remarkable high-rate capacity of 112 mAh g −1 even at 20 C. The superior electrochemical performance is mainly ascribed to the novel structure via 'ship in bottle' strategy. This unveils efficient pathways for the development of new generation super-stable organic cathode materials with excellent battery performance.